1989
DOI: 10.1007/bf01311086
|View full text |Cite
|
Sign up to set email alerts
|

HM-PAO-imaging and herpes encephalitis

Abstract: Selective uptake of the cerebral blood-flow imaging agent 99mTc-hexamethylpropyleneamine oxime (HM-PAO) by Human Herpesvirus 1 (HSV-1) infected cells was investigated in vivo and in vitro. No specific uptake of HM-PAO was observed either in encephalitic rats (by brain scintigraphic imaging or by immunoperoxidase staining/autoradiography of brain sections) or in HSV-1 infected Vero cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…constitutively over-transcribed CYP6A2, and previous work with northern and western blots has demonstrated that CYP6G1 and CYP12D1 proteins are over-expressed in Wisconsin [58]. The constitutive over-expression of any one or a combination of P450s may contribute to the Wisconsin strain being more susceptible than the Canton-S strain to H 2 O 2 because at least some P450s generate reactive oxygen species (ROS) as a by-product of catalysis [72][73][74][75], thereby increasing cellular oxidative stress. Oxidative stress is known to have negative impact on biological systems [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…constitutively over-transcribed CYP6A2, and previous work with northern and western blots has demonstrated that CYP6G1 and CYP12D1 proteins are over-expressed in Wisconsin [58]. The constitutive over-expression of any one or a combination of P450s may contribute to the Wisconsin strain being more susceptible than the Canton-S strain to H 2 O 2 because at least some P450s generate reactive oxygen species (ROS) as a by-product of catalysis [72][73][74][75], thereby increasing cellular oxidative stress. Oxidative stress is known to have negative impact on biological systems [76,77].…”
Section: Discussionmentioning
confidence: 99%